Activating Factors of Music Teachers’ Self-Education in the Postgraduate Educational System - Iryna Dubrovina (Pedagogical Discourse, 2014)
The article reveals the nature of the term “activating factor of a music teachers’ self-education». Also there has been suggested the classification of activating factors of music teachers in the postgraduate educational system.There has been analyzed the revision of the labor market’s demands concerning the personal and professional qualities of a music teacher. There has been grounded the dependence of the level of teachers’ self-skills development on gained educational level, the impact of firm factors of teachers’ self-educational activities on the level of the ability to use their proficiency. There has been determined the subject of “activating factors of teacher’s self-educational activities» as the ones which promote their personal and professional qualities to be improved and to mould a positive motivation in pedagogical art, to satisfy the needs in self-study as the value of human’s life, the way of a constant person’s self-development. There have been highlighted the dominating activating factors of self-educational activities which determine the direction of an individual professional development of a teacher and have an impact on the results of self-study and on the quality of pedagogical work. It’s been presented the conclusion about the impact of the various objective and subjective factors on the results of creative and pedagogical as well as self-educational activities of a teacher in a postgraduate educational system. In the course of the experiment it has been proved that taking into account the activating factors of teachers’ self-educational activities in a postgraduate educational system provides the planning of professional improvement, teachers’ preparation on new level which stands as the necessary component for the pedagogical work to be supporting and efficient.